Enzymes - Aleksandrova, K. V.; Krisanova, N. V.; Levich, S. V.; Александрова, Катерина Вячеславівна; Крісанова, Наталія Вікторівна; Левіч, Сергій Вадимович (Zaporizhzhya State Medical University, 2017)
This Manual was made in accordance with the program of Biological chemistry for training of students of higher educational institutions of III-IV levels of accreditation for specialty «Medicine». It is recommended to use for teachers that work with students of International Department (the second year, english medium of study).